The political irruption of short video: Is TikTok a new window for Spanish parties? (Communication & Society, 2022)
This paper analyses the use of TikTok by the main Spanish parties. The article studies the intensity of use of the short video social network by the accounts of the Partido Popular, Vox, Podemos and Ciudadanos, their narratives and themes, and the views obtained based on them. The research applies a content analysis to the videos published by these groups from account creation until the end of 2020, a period in which the PSOE had no presence. The corpus amounts to 182 units of analysis. The results show that the partisan use of TikTok is still in its infancy and that its intensive use is limited to newly emerging parties, with more favourable results for the most polarised groupings. Moreover, the parties do not adapt to the platform's own narrative codes, without this influencing the impact of their publications; the thematic diversity does have an impact, however. In general, the ideological orientation of the videos is greater than the sectoral orientation, in line with the polarisation in which Western democracies are immersed.